An Analysis of The Effect of Teaching Methods on Students' Motivation in Learning English - Oscar Ricman; Charlie Ba’ka; Elim Trika Sudarsi; Ilmiah Ibrahim; Maminiaina Andosoa Faniriana (Jurnal Dieksis ID, 2025)
English proficiency is a crucial skill in the globalization era, especially for junior high school students as a foundation for learning foreign languages. However, low student motivation remains a major challenge in English learning. This study aims to determine the extent to which teaching methods affect students’ motivation to learn English at SMP Kristen Makale. A quantitative approach with an explanatory design was employed. The population consisted of 127 seventh-grade students, from which a sample of 40 students (32%) was selected using proportional random sampling to ensure representative data across classes. Data collection techniques included observation, a structured questionnaire using a four-point Likert scale, and documentation. The data were analyzed using descriptive statistics and simple linear regression, assisted by the latest version of SPSS software. The results show that teaching methods have a significant effect on students’ learning motivation, with a coefficient of determination (R²) of 0.531 or 53.1%. The correlation coefficient (R) of 0.729 indicates a strong relationship between the variables. Lecture, demonstration, discussion, question-and-answer, and presentation methods were found to be effective in enhancing student motivation, with motivational response rates ranging from 72% to 76.8%. These findings suggest that the success of teaching methods is closely related to how well the method aligns with students' characteristics and how creatively teachers manage the learning process. Therefore, it is recommended that teachers continue to develop and apply more diverse and innovative instructional strategies to improve students' overall motivation in learning English.